Exploring the Features and Shades of Modality in an Autobiography through Corpus Patterns - Siddique, Ali Raza; Mahmood, Muhammad Asim; Ahmad, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This study explored the occurrences of modalities (i.e. boulmaic, deontic, epistemic, and perception), attitude and shades marked by the writer in an autobiography. In addition, the study tested the patterns designed to study modality in different genres. For this purpose, a corpus was developed and tagged through Parts of Speech (POS) Tagger for analysis employing AntConc 3.4.4.0 which was further interpreted in the light of Simpson’s (1993) model. The writer was observed to shape the meaning in the autobiography through different functions of modality i.e. (un)certainty, attitude, point of view, ability, possibility and probability. By using these functions, the text was made persuasive, interesting and more realistic. The incorporation of such functions marked positive and negative shades in the autobiography that led to comprehend the writer’s point of view through the text. Conclusively, the text appeared more positive than negative shaded. The positive shade was marked through deontic and boulomaic modalities that denoted alienation and uncertainty of the writer. Moreover, the application of the proposed patterns was also successful to explore the features of modality through corpus tools. The study proposed them in the form of a model for further studies.